A Team's Journey Toward More Equitable Philanthropic Research and Eval uation Practices - Spring, Kimberly; Mata, Maria Fernanda; Poirier, Jeffrey; Holmes, Allison; François, Amir (The Foundation Review, 2023)
This article describes the journey of the Research and Evaluation team at the Annie E. Casey Foundation to develop an approach that would al low us to rethink and deepen how we, as funders of research and evalua tion, center equity in our practice. In particular, we explain how, th rough this process, we began to focus on what it means to orient resea rch and evaluation toward participant owners and came to examine the a ssumptions, expectations, habits, and values that we held. These exper iences have presented us with opportunities to learn and be open to ne w ways of engaging in our work. We illustrate what this has looked lik e through vignettes involving five different Casey Foundation research and evaluation projects and conclude with some of the core lessons th at we have learned: View tension as an opportunity for creativity; bui ld in and protect space and time for reflection; and develop rapport a nd trust to strengthen practice.